A correlational study of attitudes toward mathematics and academic performace. - Saromines, Juliet M (1998.)
This study was undertaken to determine the relationship between attitudes towards mathematics and academic performance among UPV students. Specifically, it sought to answer the following question: (1)does sex of the students affect attitudes towards mathematics and academic performance? (2)is there a positive relationship between attitudes toward mathematics and academic performance? The sample was taken from a population of UPV Miag-ao students who took Math 11, an algebra course, during the first semester Ay 1997 - 1998 and were officially registered for the second semester Ay 1997 - 1998. They were chosen through stratified random sampling with proportional allocation. The T - test and Pearson product Movement Correlation was used at 0.05 level of significance. The result showed that there was no significant difference between the attitudes of males and females towards mathematics and their performance in mathematics was not in significant difference. Attitudes towards mathematics and academic performance were negatively correlated and with no significant difference.
Research Paper (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Students -- UPV-CAS.